Pelatihan Penggunaan Aplikasi Spss dalam Mengelola Data Penelitian pada Mahasiswa Inisma Jambi - Erwin, Geiskha; Jingga, Lara (Institut Nalanda, 2024)
The lack of understanding and ability of Inisma Jambi students in using SPSS software as a statistical test tool made us feel the need to provide training on how to use the SPSS program and how to analyze the results of the program. The main purpose of implementing this activity is to provide basic knowledge on how to process statistical data. Share information on how to use SPSS to process statistical data. Provide information on how to understand the results of statistical data that has been processed. After completing the SPSS training, students are expected to be able to use SPSS to process statistical data better, and this will improve the quality of their studies and scientific writing. The expected benefits of carrying out this activity are: students can learn about the principles of processing statistical data. Students learn how to use SPSS to analyze statistical data. Training on statistical data processing with the SPSS program for students at Inisma Jambi shows that their understanding has improved after participating in the training. They also have the motivation to conduct research with quantitative methods and can use the SPSS application themselves.